Working for God: Religion and Occupational Crime and Deviance. Issue 2 (1st February 2023) - Desmond, Scott A.; Rorie, Melissa; Sohoni, Tracy
ABSTRACT: Although previous research suggests that many dimensions of religion (e.g., religious service attendance, importance of religion) are significantly related to juvenile delinquency and substance use, fewer studies have examined the relationship between religiosity and adult crime, particularly white-collar crimes. Based on Wave 4 of the Baylor Religion Survey, we used Ordinary Least Squares (OLS) regression to determine if religiosity reduces occupational crime and deviance due to feelings of work as a vocational calling which we hypothesized would increase job satisfaction and affective commitment to work. We find that people who attend religious services more frequently are significantly less likely to engage In occupational crime and deviance, but importance of religion is not significantly related to occupational crime or deviance. Contrary to our expectations, vocational calling, job satisfaction, and affective commitment do not explain the relationship between religious service attendance and occupational crime and deviance. Our research suggests future research is warranted to better understand the relationship between religion and adult crime, particularly white-collar crime, and the possible mediating factors that may explain this relationship.